2016
DOI: 10.1039/c5ra19455e
|View full text |Cite
|
Sign up to set email alerts
|

Photoluminescence of Cr3+ in nanostructured Al2O3 synthesized by evaporation using a continuous wave CO2 laser

Abstract: Photoluminescence of Cr3+ in nanostructured α-Al2O3 synthesized by evaporation using a continuous wave CO2 laser.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 33 publications
2
8
0
Order By: Relevance
“…[32][33][34]62 While the change in both PL and transmission due to implantation spans over a large range of wavelengths, interestingly, the characteristic Cr 3+ impurity peak shown in Figure 3b is unaffected by the implantation process, hence suggesting a wider energy distribution of trap states in the bandgap as compared to atomic transition levels. 63,64 As a result, the implantation process results in a broad photoluminescence band, which is in agreement with what has been reported for ion-implanted Al 2 O 3 . 33 The luminescence of the implanted regions is higher than that of pristine sapphire at shorter wavelengths (see the curves for 532 and 633 nm excitation wavelengths in Figure 3a): this suggests the formation of optically active defect states deep in the oxide bandgap.…”
Section: ■ Results and Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…[32][33][34]62 While the change in both PL and transmission due to implantation spans over a large range of wavelengths, interestingly, the characteristic Cr 3+ impurity peak shown in Figure 3b is unaffected by the implantation process, hence suggesting a wider energy distribution of trap states in the bandgap as compared to atomic transition levels. 63,64 As a result, the implantation process results in a broad photoluminescence band, which is in agreement with what has been reported for ion-implanted Al 2 O 3 . 33 The luminescence of the implanted regions is higher than that of pristine sapphire at shorter wavelengths (see the curves for 532 and 633 nm excitation wavelengths in Figure 3a): this suggests the formation of optically active defect states deep in the oxide bandgap.…”
Section: ■ Results and Discussionsupporting
confidence: 90%
“…These measurements supporting the argument for the ion damage-induced formation of trap states within the oxide bandgap 47,48 . While the change in both PL and transmission due to implantation spans over a large range of wavelengths, interestingly, the characteristic Cr 3+ impurity peak shown in Figure 3b is unaffected by the implantation process, hence suggesting a wider energy distribution of trap states in the bandgap, as compared to atomic transition levels 49,50 .…”
Section: Charge Transportmentioning
confidence: 99%
“…4A2 in Cr 3þ ions of the -Al 2 O 3 matrix (the R1 and R2 lines), whereas for oxidation temperatures at 700 C, curves have a pronounced maximum at about max ¼ 694 nm. This shift was shown by Kostyukov et al [53][54][55] The PL results of PM2000 alloy oxidized at 700 C, and that oxidized at 1200 C re°ects the di®erences of oxides formed at each temperature. The results of antecedent work 55 have shown that at 700 C, the various oxides formed are essentially Fe 2 O 3 , Cr 2 O 3 and Al 2 O 3 .…”
Section: Photoluminescence Spectroscopysupporting
confidence: 54%
“…In excitation (PLE) spectra (Figure 8a), bands at 325 nm corresponded to the PZ and/or Al 2 O 3 substrate and to charge transfer bands (CTB) and also to the spin‐allowable Cr 3+ changes, respectively. [ 25,26 ] The PLE spectra for Cr 3+ (λ em = 614 and 714 nm) exhibited broad bands at 403 and 545 nm, which were attributed to spin‐allowed transitions from the 4 A 2 ground state to the 4 T 1 and 4 T 2 excited states, respectively. [ 27,28 ] The small band at 475 nm was linked to the 4 A 2 → 2 T 2 spin forbidden transition.…”
Section: Resultsmentioning
confidence: 99%
“…In Figure 7 and also to the spin-allowable Cr 3+ changes, respectively. [25,26] The PLE spectra for Cr 3+ (λ em = 614 and 714 nm) exhibited broad bands at 403 and 545 nm, which were attributed to spin-allowed transitions from the 4 A 2 ground state to the 4 T 1 and 4 T 2 excited states, respectively. [27,28] The small band at 475 nm was linked to the 4 A 2 !…”
Section: Morphological Characteristics Of Filmsmentioning
confidence: 99%